Can Renal Parameters Predict the Mortality of Hospitalized COVID-19 Patients? - Eli Zolotov; Anat Sigal; Martin Havrda; Karolína Jeřábková; Karolína Krátká; Nikola Uzlová; Ivan Rychlík (Karger Publishers, 2022)
Introduction: Our study aimed to analyze whether renal parameters can predict mortality from COVID-19 disease in hospitalized patients. Methods: This retrospective cohort includes all adult patients with confirmed COVID-19 disease who were consecutively admitted to the tertiary hospital during the four-month period (1.9. - 31.12.2020). We analyzed their basic laboratory values, urinalysis, comorbidities, length of hospitalization, and survival. The RIFLE and KDIGO criteria were used for AKI and CKD grading, respectively. To display renal function evolution and the severity of renal damage, we subdivided patients further into 6 groups as follows: group 1 (normal renal function), group 2 (CKD grade 2+3a), group 3 (AKI-DROP defined as whose s-Cr dropped by >33.3% during the hospitalization), group 4 (CKD 3b), group 5 (CKD 4+5) and group 6 (AKI-RISE defined as whose s-Cr was elevated by ≥ 50% within 7 days or by ≥26.5 μmol/L within 48-hours during hospitalization). Then, we used eGFR on admission independently of renal damage to check whether it can predict mortality. Only 4 groups were used: Group I - normal renal function (eGFR>1.5 ml/s), group II mild renal involvement (eGFR 0.75-1.5), group III - moderate (eGFR 0.5-0.75) and group IV - severe (GFR<0.5). Results: 680 patients were included in our cohort. 244 patients displayed normal renal function, 207 patients fulfilled AKI, and 229 patients suffered from CKD. In total, a significantly higher mortality rate was found in the AKI and the CKD groups vs. normal renal function - 37.2% and 32.3% vs. 9.4%, respectively (P<0.001). In addition, the groups 1-6 divided by severity of renal damage reported mortality as 9.4%, 21.2%, 24.1%, 48.7%, 62.8% and 55.1%, respectively (P<0.001). The mean hospitalization duration of alive patients with normal renal findings was 9.5 days, while 12.1 days in patients with any renal damage (P<0.001). When all patients were compared according to eGFR on admission, the mortality was as follows: Group I (normal) 9.8%, Group II (mild) 22.1%, group III (moderate) 40.9% and group IV (severe) 50.5%, respectively (P<0.001). It was a significantly better mortality predictor than CRP on admission (AUC 0.7053 vs. 0.6053). Conclusions: Mortality in patients with abnormal renal function was 3 times higher compared to patients with normal renal function. Also, patients with renal damage had a worse and longer hospitalization course. Lastly, eGFR on admission, independently of any renal damage, was an excellent tool for predicting mortality. Further, the change in s-Cr levels during hospitalization reflected the mortality prognosis.